Aspects socio- et psycholinguistiques de la modélisation de la compréhension des textes de la vie quotidienne: fait divers et publicité - Miczka, Ewa (Studia Romanica Posnaniensia, 2007)
The author’s aim is to study understanding of text as process, within text linguistics, with consideration of the main factors which condition it. The author concentrates her attention mainly on the phenomenon of the reader’s constant referring to the text which he interprets to the information previously acquired by him.